Catalytic hydrogenation of isophthalonitrile (IPN) over supported monometallic and bimetallic catalysts. Issue 71 (2nd August 2015) - Liu, Chang; Li, Xiaodan; Wang, Tiefeng
<x xml:space="preserve">Abstract</x> The Ni–Fe/γ-Al2O3 bimetallic catalyst showed enhanced activity and m-XDA selectivity in hydrogenation of IPN, due to strong N–metal interaction and weak H adsorption strength.